Pag-unlad tatlong taon pabalik, limang taon paharap - Aguilar, Mila D.; Catholic Bishops Conference of the Philippines; Institute for Filipino Cinema; National Secretariat for Social Action and Justice and Peace ([Quezon City] The Institute, 1989)
Traces the Philippine socio-economic development, three years before and five years after 1989, from the vantage point of experts, government officials, businessmen, and ordinary consumers and housewives.
VHS
Host, Ma. Ernie Selvido, editor, Mel L. Bacani III
Keywords: Philippines -- Economic conditions; Philippines -- Social conditions; Sociology